PENGARUH LINGKUNGAN KERJA TOKSIK TERHADAP STRES KERJA PADA PT. MACHIA JAYA AMBON - Lidya Dwi Indasari Siahaya; Stenly Ronaldo Titioka; Elsina Huberta Aponno (P3M Politeknik Negeri Ambon, 2026)
This reasearch aims to determine the effect of a toxic work environment on employee work stress at PT. Machia Jaya Ambon. The research was conducted in response to identified issues indicating the presence of a toxic or unhealthy work environment among employees. This condition ultimately affects employee stress levels in terms of time and energy, impacting the company as a whole.This is an empirical study involving the entire population of employees at PT. Machia Jaya Ambon. The research sample consists of 51 respondents, excluding management. The analytical technique used is simple linear regression analysis.The results show that a toxic work environment has a positive and significant effect on employee work stress at PT. Machia Jaya Ambon. This means that the worse the work environment experienced by employees, the higher the level of work stress they tend to exhibit.Keywords: Toxic Work Environment, Work Stress.